2005
DOI: 10.1111/j.0742-2822.2005.03168.x
|View full text |Cite
|
Sign up to set email alerts
|

Freehand Three‐Dimensional Echocardiography with Rotational Scanning for Measurements of Left Ventricular Volume and Ejection Fraction in Patients with Coronary Artery Disease

Abstract: Three-dimensional echocardiography using magnetic tracking system and average rotational geometry offered a feasible and accurate method for quantification of LV volumes and EF in patients with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…As one would expect, numerous patients with "acceptable" filling pressures (from the PAC) did in fact have inadequate filling. This reaffirms what is previously stated in acidotic conditions with impairment of ventricular performance and the lack of tissue oxygenation (47,(65)(66)(67)(68).…”
Section: Effect and Importance Of Echocardiographysupporting
confidence: 90%
“…As one would expect, numerous patients with "acceptable" filling pressures (from the PAC) did in fact have inadequate filling. This reaffirms what is previously stated in acidotic conditions with impairment of ventricular performance and the lack of tissue oxygenation (47,(65)(66)(67)(68).…”
Section: Effect and Importance Of Echocardiographysupporting
confidence: 90%
“…LV mass was calculated by the ASE 17 method according to recommendations of the American Society of Echocardiography 18 . Freehand 3D echocardiography was performed in each subject using equipment and methods that have been described previously, 19 and validated with explanted hearts, 14 magnetic resonance imaging, 19 and myocardial perfusion gated SPECT 20,21 …”
Section: Methodsmentioning
confidence: 99%
“…With advances in real-time 3-D echocardiography, calculation of LV volume has become more accurate than with 2-D echocardiography. 2,11,12 Volumetry by 2-D echocardiography depends on geometric assumptions and is subject to image-plane positioning errors. In conditions where the LV is distorted in shape such as after an AMI and ischemic cardiomyopathy, LV assessment is not accurate using 2-D methods.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In conditions where the LV is distorted in shape such as after an AMI and ischemic cardiomyopathy, LV assessment is not accurate using 2-D methods. 11,12 Recently, Mannaerts et al 6 reported that 3-D DSI is >25% in the acute stage of an AMI identified patients who developed remodeling 6 or 12 months after AMI. In addition, they also found that 3-D EDV and ESV were also predictors of impending LV remodeling after AMI.…”
Section: Previous Studiesmentioning
confidence: 99%